Analisis Kesalahan Pelafalan Perubahan Tona “Bu” Bahasa Mandarin - Wikarti, Aprilia Ruby (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2022)
Abstract:In tonal languages such as Mandarin, tone is a suprasegmental phoneme that can distinguish meaning. A certain syllable can undergo a change in tone, depending on the syllable that comes after it. One of the changes in tone that often occurs is the change in tone bu, which means "no". This study aims to find out the forms and causes of pronunciation errors in the change in tone bu in Mandarin learners. The research data was taken from the audio recordings of 12 students of the Advanced Reading and Writing I Study Program of the Chinese Language Education Study Program, State University of Jakarta. The method used is an error analysis method with a qualitative approach. The results showed that there were phonological errors, with the cause of the error being the result of negative transfer of understanding the target language and negative transfer of mother tongue.